Implementation Of Sustaining Innovation In Village Financial Management As A Strategy To Improve Village Governance - Ida Yusnita; Zachari Abdallah; Ayu Esteka Sari (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study investigates the structural relationship between sustaining innovation, strengthening village financial management, and good village governance in Kerinci Regency, Indonesia. Using Structural Equation Modeling (SEM) with data collected from 285 villages across 18 districts, the analysis reveals that strengthening financial management does not significantly influence sustaining innovation (β = 0.061, R² = 0.004), indicating that improvements in transparency, accountability, and efficiency alone are insufficient to enhance innovation capacity within village institutions. Likewise, the direct effect of financial management on governance performance remains marginal (β = 0.059). In contrast, sustaining innovation demonstrates a strong and significant impact on good village governance (β = 0.459, R² = 0.218), confirming that continuous improvement, capability enhancement, and service quality constitute the primary drivers of governance transformation. At the indicator level, transparency (λ = 1.092) and efficiency (λ = 0.969) emerge as the most dominant components of financial management, while capability enhancement (λ = 1.015) and service quality (λ = 0.931) are the strongest indicators shaping sustaining innovation. Overall, the findings underscore the centrality of innovation as the key determinant of village governance quality, exceeding the influence of financial administrative mechanisms. These results provide crucial policy implications, particularly in strengthening human resource capacity, accelerating digital transformation, and institutionalizing innovation-based governance frameworks in rural settings.